Exploring The Influence of Online Inquiry Learning With E-scaffolding Prompting Question on Problem-Solving Skills in The Work Energy Topic for Islamic Senior High School Students - Arrika Wifqotu Lailin Nafisah; Supriyono Koes Handayanto; Sunaryono Sunaryono; Chokchai Yuenyong (Jurnal Pendidikan Sains, 2023)
This comprehensive investigation delves into the impact of integrating e-scaffolding prompting questions into online inquiry learning on students' problem-solving skills (PSS). With an explanatory design and a mixed-methods approach, the study focuses on XI-MIPA class students at MAN 1 Kediri City during the academic year 2022-2023. Utilizing meticulously crafted learning instruments, five problem-solving skills questions, and precise interview guidelines, the research employs triangulation through pre-tests, post-tests, and in-depth interviews. Quantitative data undergoes rigorous scrutiny via Analysis of Covariance (ANCOVA). The primary objective is to unveil the discernible influence of online inquiry learning complemented by e-scaffolding on the nuanced domain of PSS. Employing quasi-experimental methodologies, the study systematically compares a class engaged in conventional direct learning with one immersed in the intricacies of online inquiry learning. ANCOVA results decisively highlight a statistically significant disparity in PSS, with the online inquiry learning cohort consistently outperforming the control group. The granular analysis extends to specific problem-solving processes, delineating stages like problem identification, physics-rooted strategic planning, application of problem-solving strategies, mathematical procedures, and critical evaluation. The experimental cohort consistently surpasses the control group across these facets, affirming the pronounced efficacy of online inquiry learning enhanced by e-scaffolding. Qualitative insights from meticulously structured interviews corroborate quantitative findings, revealing a methodical and structured problem-solving approach within the experimental group. A discernable emphasis on conceptual reasoning emerges, reflective of a profound understanding nurtured by the synergistic amalgamation of online inquiry learning and e-scaffolding. The study conclusively advocates for the widespread implementation of this pedagogical framework as a transformative tool to enhance PSS across diverse physics topics. The implications extend to providing a robust foundation for future scholarly investigations, fortified by empirical evidence supporting the affirmative impact of online inquiry learning with e-scaffolding on students' problem-solving skills in physics education.DOI: 10.17977/jps.v11i22023p045